2015
DOI: 10.1103/physreva.92.013816
|View full text |Cite
|
Sign up to set email alerts
|

Giant anomalous self-steepening in photonic crystal waveguides

Abstract: Self-steepening of optical pulses arises due the dispersive contribution of the χ (3) (ω) Kerr nonlinearity. In typical structures this response is on the order of a few femtoseconds with a fixed frequency response. In contrast, the effective χ (3) Kerr nonlinearity in photonic crystal waveguides (PhCWGs) is largely determined by the geometrical parameters of the structure and is consequently tunable over a wide range. Here we show self-steepening based on group-velocity (group-index) modulation for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The black dashed line indicates simulations with suppressed FCD showing the pulse shifts noticeably less in this case and we conclude that FCD causes the temporal advance. We suspect the remaining shift might be due to strong self-steepening in the photonic crystal [13] or residual pulse chirp. More recently we showed that FCD can induce soliton fission [14].…”
Section: Weak Free Carrier Regime (3pa-limited)mentioning
confidence: 98%
“…The black dashed line indicates simulations with suppressed FCD showing the pulse shifts noticeably less in this case and we conclude that FCD causes the temporal advance. We suspect the remaining shift might be due to strong self-steepening in the photonic crystal [13] or residual pulse chirp. More recently we showed that FCD can induce soliton fission [14].…”
Section: Weak Free Carrier Regime (3pa-limited)mentioning
confidence: 98%
“…Two reasons confer on this work the potential to open a new avenue in nonlinear guided optics. First, experimental tests of self-steepening effects predicted theoretically, ranging from MI cancellation and CSC in the long pulse regime, as studied here, to soliton self-frequency shift deceleration [36], on-chip octave-spanning SC generation [37], or even anomalous self-steepening [38], become now feasible using ps sources and more accessible technologies, as silicon-on-insulator (SOI) is, unlike previous approaches [37,38]. Second, these results might also be feasible at telecom [39] or visible wavelenghts [40] where chalcogenides [41] and diamond [42] possess their 2PA resonance.…”
mentioning
confidence: 97%
“…Accurate modelling of pulse propagation through photonic crystal waveguides in the slow light regime requires taking into account the dispersion in the effective nonlinearity strength, which can induce effects such as pulse self-steepening and supercontinuum generation [28][29][30][31]. Despite the proven importance of these effects in applications [32][33][34], analysis of nonlinear light propagation in topological photonic structures most often assumes non-dispersive nonlinearities, in both the underlying material response [35][36][37][38][39][40][41][42][43][44][45] and effective models describing the propagation of nonlinear edge states [46][47][48][49][50].…”
mentioning
confidence: 99%